Dietary patterns of 18–month old infants in Singapore - Eu, Li Juan (Nanyang Technological University, 2014)
The Growing Up in Singapore Towards healthy Outcomes (GUSTO) study is the first population-based birth cohort in Singapore designed to understand the developmental origins of health and disease from an Asian perspective. Existence of the three major ethnic groups (Chinese, Malay and Indian) in Singapore present a perfect setting to examine dietary habits of Asian infants. By using a common data collection approach in a diversity of ethnic groups within a single study, interethnic comparisons can be made. For this project, a semi-quantitative food frequency questionnaire (SFFQ) designed by GUSTO for the 18-month old (M18) infants will be analyzed for identifying dietary patterns and consumption of key foods and food groups. The objectives are to transform information in the questionnaires into quantifiable values and by using statistical tools to analyze the data and at the same time, relate with economic and socio-demographic characteristics. Two patterns were defined: “Convenience food” and “Traditional food”. Results showed that the Malays (p=0.018) and younger mothers (p=0.033) follow more closely to “convenience food” pattern which consisted of foods that require less preparation time. This supported the theory that maternal demographic factors and the child’s early dietary patterns are associated.